A agricultura no nordeste brasileiro: Oportunidades e limitaç\~oes ao desenvolvimento - César Nunes de Castro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– Farming in Brazil is historically one of the main bases of the country's economy. In northeastern Brazil, agriculture has an important role in the regional economy, with the aim of this study to evaluate the recent situation of agriculture in the Northeastern region in order to identify constraints and opportunities for development and discuss public policy proposals that can contribute to the expansion of regional agricultural production. Several factors are often referred as potential barriers to the development of agriculture in this region, including environmental issues, disability in logistics, technological backwardness, lack of credit, lack of technical assistance, among others. Overall, most agricultural production activities in the Northeast has low yield outcomes, among the causes of this scenario includes issues such as a crisis of investment and the difficulty of producers to intensify their production systems.
Keywords: Q1; Q10; 330; agriculture; Northeast region; development; Landwirtschaft; Landwirtschaftliche Entwicklung; Brasilien (Nordost)